2018
DOI: 10.1111/jfs.12529
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Guar and Tragacanth gums as edible coatings in Cheddar cheese during ripening

Abstract: The aim of this study was to evaluate a Guar/Tragacanth gum‐based edible coating used on Cheddar cheese during ripening for 90 days. Five samples of Cheddar cheese blocks were coated by different coating materials in triplicate as following: C, coated with polyvinyl acetate as control, GC, coated with 1% Guar gum and TG1, TG2, and TG3, coated with 0.75, 1, and 1.25% Tragacanth gum, respectively. All samples were kept at 8 ± 2 °C for 90 days. The results showed that total mesophilic aerobic bacteria counts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The results of this study are consistent with those reported by Pourmolaie et al. (2018), which concluded the sensory properties of edible coated cheddar cheese were not affected, there was no significant difference between samples with or without coating. On the other hand, in studies of Ksouda et al.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study are consistent with those reported by Pourmolaie et al. (2018), which concluded the sensory properties of edible coated cheddar cheese were not affected, there was no significant difference between samples with or without coating. On the other hand, in studies of Ksouda et al.…”
Section: Resultssupporting
confidence: 93%
“…Cavalcante et al (2007) had scores ranging between 6.81 and 7.38, while studying coalho cheese with pasteurized milk and endogenous culture. The results of this study are consistent with those reported by Pourmolaie et al (2018), which concluded the sensory properties of edible coated cheddar cheese were not affected, there was no significant difference between samples with or without coating. On the other hand, in studies of Ksouda et al (2019), the coated cheese samples were more appreciated by the tasters with high averages for flavor and aroma attributes compared to uncoated cheeses.…”
Section: Sensory Analysis and Purchase Intensionsupporting
confidence: 92%
See 1 more Smart Citation
“…They observed that the use of concentrations of 1% of galactomannan, 0.2% EO, and 0.1% polysorbate inhibited mesophilic aerobes bacteria (<10 log CFU). Cheddar cheese was coated with solutions of GG (1% GG, 50% glycerol), and TG (0.75, 1, and 1.25%) stored at 8 to 2 for 90 days were followed by Pourmolaie et al 115 Cheese coated with 3% of TG showed the highest content of soluble nitrogen in TCA and tyrosine, tryptophan amino acids, C14:1 and C18:0 fatty acids. The possible numbers of nonstarter lactic acid bacteria were considerably higher in the control and coated cheese (1.25% TG) due to limitation of air movement between the external environment and the cheese texture through reduction of relative oxygen pressure.…”
Section: Plant Gums For the Coating Of Dairy Productmentioning
confidence: 99%
“…Several efforts with essential oils and plant extracts have been performed to preserve cheese, and some of them focus on enhancing raw milk preservation [12] and its role during cheesemaking as an alternative food additive [13,14] due to the presence of several bioactive compounds such as phenolics and terpenes with broad-spectrum antimicrobial activity. On the other hand, in the last decade, edible film coatings in food packaging [15,16] also have become a reality in commercial applications of cheese preservation in order to ensure quality and safety in the industry since they can reduce weight loss, prevent cheese spoilage, and control respiratory rate [17][18][19][20]. In addition, edible films/coatings were also very recently examined as the most widely used system for delivering essential oils/extracts as potential preservatives and antioxidants in cheese [21].…”
Section: Introductionmentioning
confidence: 99%